Efektivitas Model Problem Based Learning dan Problem Solving Terhadap Kemampuan Berpikir Kreatif Tematik Kelas V Semester II Tahun 2019/2020 - Ellen Dinda Saraswati; Tego Prasetyo (Jurnal Ilmiah Wahana Pendidikan, 2020)
Abstract: This study aims to determine the effectiveness of the application of the Problem Based Learning and Problem Solving learning models to the creative thinking skills of the fifth grade elementary school. In this study there are 3 classes, namely the experimental class I in SD Negeri 1 Tanggung using the Problem Based Learning treatment, the experimental class II in SD Negeri 3 Tanggung using the Problem Solving treatment, and the control class in SD Negeri 4 Tanggung for which no treatment was given. The instruments used were observation, questionnaires, and tests. Based on the data obtained the results of the analysis showed a significant difference between the percentage of questionnaires that were reviewed based on the category of students' creative thinking level, in the experimental class I questionnaire percentage was 90.65% (very good) for the experimental class II the questionnaire percentage was 71.4% ( good) and in the control class the percentage of questionnaires was 53.75% (enough). This shows that there is a significant difference in effectiveness between the creative thinking abilities of fifth grade students using the Problem Based Learning and Problem Solving models. Keywords: Problem Based Learning, Problem Solving, Creative Thinking Skills